Competitive interactions of two parasitic wasps that require the same host - Vyas, Dhaval Kartik, author; Ode, Paul J., advisor; Angeloni, Lisa, committee member; Bjostad, Louis B., committee member; Ghalambor, Cameron K., committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: biological control; foraging; parasitoid; competition; animal behavior; hyperparasitoid